Application of aptamers in regenerative medicine - Luo, Zhaohui; Chen, Shimin; Zhou, Jing; Wang, Chong; Li, Kai; Liu, Jia; Tang, Yujin; Wang, Liqiang (Frontiers in Bioengineering and Biotechnology, 2022)
Regenerative medicine is a discipline that studies how to use biological and engineering principles and operation methods to repair and regenerate damaged tissues and organs. Until now, regenerative medicine has focused mainly on the in-depth study of the pathological mechanism of diseases, the further development and application of new drugs, and tissue engineering technology strategies. The emergence of aptamers has supplemented the development methods and types of new drugs and enriched the application elements of tissue engineering technology, injecting new vitality into regenerative medicine. The role and application status of aptamers screened in recent years in various tissue regeneration and repair are reviewed, and the prospects and challenges of aptamer technology are discussed, providing a basis for the design and application of aptamers in long-term transformation.